2012
DOI: 10.1128/aem.07637-11
|View full text |Cite
|
Sign up to set email alerts
|

Abundance, Distribution, and Activity of Fe(II)-Oxidizing and Fe(III)-Reducing Microorganisms in Hypersaline Sediments of Lake Kasin, Southern Russia

Abstract: ABSTRACTThe extreme osmotic conditions prevailing in hypersaline environments result in decreasing metabolic diversity with increasing salinity. Various microbial metabolisms have been shown to occur even at high salinity, including photosynthesis as well as sulfate and nitrate reduction. However, information about anaerobic microbial iron metabolism in hypersaline environments is scarce. We studied the phylogenetic diversity, distribution, and metabolic activity of iron(II)-ox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
58
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 85 publications
(60 citation statements)
references
References 90 publications
1
58
1
Order By: Relevance
“…The domination of Firmicutes in PS is not in agreement with the opinion that Bacteroidetes is the most abundant bacterial phylum in clone libraries from crystallizer ponds [25,26]. According to Ant on et al [8], the presence of different bacterial taxa in them could be due either to their import from previous ponds with lower salinity or to their active growth in the crystallizers.…”
Section: Salt Composition Of Watermentioning
confidence: 47%
“…The domination of Firmicutes in PS is not in agreement with the opinion that Bacteroidetes is the most abundant bacterial phylum in clone libraries from crystallizer ponds [25,26]. According to Ant on et al [8], the presence of different bacterial taxa in them could be due either to their import from previous ponds with lower salinity or to their active growth in the crystallizers.…”
Section: Salt Composition Of Watermentioning
confidence: 47%
“…Almost nothing is known about the abundance and activity of nitratereducing Fe(II) oxidizers in marine habitats. It was shown by Emmerich et al (45) that nitrate-reducing Fe(II) oxidizers can be found in hypersaline lake sediments, and Rowe et al (46) showed that microorganisms present in marine sediment have the capability to oxidize solid-phase Fe(II) with nitrate.…”
mentioning
confidence: 99%
“…Microbial dissimilatory Fe(III) reduction plays an important role in the geochemical cycling of iron and organic matter in ano xic ecological system [14]. Iron-reducing microbes generally belong to the genera Shewanella, Geobacter, Geovibrio, Desulfobulbus etc [15][16][17]. If bacterial reduction method is successful, cost intensive method of ore roasting process can be eliminated.…”
Section: Introductionmentioning
confidence: 99%